Body site microbiota of Magellanic and king penguins inhabiting the Strait of Magellan follow species-specific patterns - Manuel Ochoa-Sánchez; Eliana Paola Acuña Gomez; Lucila Moreno; Claudio A. Moraga; Katherine Gaete; Luis E. Eguiarte; Valeria Souza (PeerJ, 2023)
Animal hosts live in continuous interaction with bacterial partners, yet we still lack a clear understanding of the ecological drivers of animal-associated bacteria, particularly in seabirds. Here, we investigated the effect of body site in the structure and diversity of bacterial communities of two seabirds in the Strait of Magellan: the Magellanic penguin (Spheniscus magellanicus) and the king penguin (Aptenodytes patagonicus). We used 16S rRNA gene sequencing to profile bacterial communities associated with body sites (chest, back, foot) of both penguins and the nest soil of Magellanic penguin. Taxonomic composition showed that Moraxellaceae family (specifically Psychrobacter) had the highest relative abundance across body sites in both penguin species, whereas Micrococacceae had the highest relative abundance in nest soil. We were able to detect a bacterial core among 90% of all samples, which consisted of Clostridium sensu stricto and Micrococcacea taxa. Further, the king penguin had its own bacterial core across its body sites, where Psychrobacter and Corynebacterium were the most prevalent taxa. Microbial alpha diversity across penguin body sites was similar in most comparisons, yet we found subtle differences between foot and chest body sites of king penguins. Body site microbiota composition differed across king penguin body sites, whereas it remained similar across Magellanic penguin body sites. Interestingly, all Magellanic penguin body site microbiota composition differed from nest soil microbiota. Finally, bacterial abundance in penguin body sites fit well under a neutral community model, particularly in the king penguin, highlighting the role of stochastic process and ecological drift in microbiota assembly of penguin body sites. Our results represent the first report of body site bacterial communities in seabirds specialized in subaquatic foraging. Thus, we believe it represents useful baseline information that could serve for long-term comparisons that use marine host microbiota to survey ocean health.